Sixteen overlooked open clusters in the four th Galactic quadrant A combined analysis of UBVI photometry and Gaia DR2 with ASteCA - Perren, Gabriel Ignacio (2020)
Aims. This paper has two main objectives: (1) To determine the intrinsic properties of 16 faint and mostly unstudied open clustersin the poorly known sector of the Galaxy at 270◦−300◦ to probe the Milky Way structure in future investigations. (2) To addresspreviously reported systematics in Gaia DR2 parallaxes by comparing the cluster distances derived from photometry with thosederived from parallaxes.Methods. Deep UBVI photometry of 16 open clusters was carried out. Observations were reduced and analyzed in an automaticway using the ASteCA package to obtain individual distances, reddening, masses, ages, and metallicities. Photometric distances werecompared to those obtained from a Bayesian analysis of Gaia DR2 parallaxes.Results. Ten out of the sixteen clusters are true or highly probable open clusters. Two of them are quite young and follow the traceof the Carina Arm and the already detected warp. The remaining clusters are placed in the interarm zone between the Perseus andCarina Arms, as expected for older objects. We found that the cluster van den Berg-Hagen 85 is 7.5 × 109 yr old, which means that itis one of the oldest open clusters detected in our Galaxy so far. The relationship of these ten clusters with the Galaxy structure in thesolar neighborhood is discussed. The comparison of distances from photometry and parallaxes data in turn reveals a variable level ofdisagreement.Conclusions. Various zero-point corrections for Gaia DR2 parallax data recently reported were considered for a comparison betweenphotometry- and parallax-based distances. The results tend to improve with some of these corrections. Photometric distance analysissuggests an average correction of ∼+0.026 mas (to be added to the parallaxes). The correction may have a more intricate dependenceon distance, but addressing this level of detail will require a larger cluster sample.